PROBLEMATIKA DAN UPAYA GURU DALAM MENERAPKAN KURIKULUM MERDEKA PADA PEMBELAJARAN MATEMATIKA - Saputri, Resky Adila; Fendiyanto, Petrus (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2025)
The purpose of this study is to determine the problems faced by teachers in implementing the independent curriculum in mathematics learning for class VIII at SMP Negeri 6 Samarinda and the efforts to overcome them. This study is a qualitative descriptive study. The subjects of the study were two mathematics teachers for class VIII at SMP Negeri 6 Samarinda, the curriculum vice principal, and six students. The objects of the study were the problems faced by teachers in implementing the independent curriculum in mathematics learning for class VIII at SMP Negeri 6 Samarinda and the efforts to overcome them. Data collection was carried out using observation, interview, and documentation techniques. The data analysis techniques used were data reduction, data presentation, and conclusion. The results of this study indicate that in implementing the independent curriculum, teachers experience problems in planning, implementing, and assessing learning. Problems in learning planning include: (1) analyzing Learning Achievements (CP) to compile Learning Objective Flow (ATP), (2) implementing diagnostic assessments, (3) compiling teaching modules, (4) compiling LKPD, (5) using teaching materials, and (6) compiling and determining Learning Objective Achievement Criteria (KKTP). Problems in implementing learning include: (1) implementing differentiated learning, (2) using technology, (3) learning atmosphere, and (4) adjusting teaching modules. Problems in learning assessment are planning and implementing assessments. Then the efforts made are: (1) socialization and training for competency development, (2) supervision and monitoring, (3) developing cooperation, and (4) supporting the school environment.